Resistência à corrosão de ligas metálicas biocompatíveis em soluções simuladoras de fluido corporal - Sales, Vinicius de Oliveira Fidelis (2019)
Metal and biocompatible metal alloys are among the materials most used as the basis to produce orthopedic prosthesis of hip, knee and implants such as the coronary stent, due to their mechanical properties and biocompatibility, required for such applications. In the long term, implanted metal materials can suffer from the corrosion process and release metallic ions in the body, causing serious problems for the patient, such as toxic reactions and chronic allergies. In this sense, the present work has the objective of analyzing the behavior of three metallic alloys used in implants: AISI 316L, CoCrMo and Ti6Al4V produced using the Direct Metallic Laser Sintering (DMLS) an additive technique (MA). For comparison, another additive manufacturing technique (MA) was used in a sample of Ti6Al4V, Electron Beam Melting (EBM). Three working electrodes were prepared for each alloy and used as an auxiliary electrode, a reference platinum plate, an electrode (Ag / AgCl (sat KCl 3M )). The electrolytes were body fluid simulator solutions: Phosphate Buffered Saline (PBS), Blood Plasma Simulator (SBF) and Artificial Saliva. These were maintained at 37 ° C, and had their pH adjusted between 6.5 - 7.5. To evaluate the corrosion resistance of the materials, the techniques of open circuit potential (OCP), potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), chronoamperometry and Mott-Schottky capacitance measurements were performed. For microstructural characterization, analysis of optical microscopy and scanning electron microscopy were performed. From the results, higher impedance values were observed for the AISI 316L alloy in relation to the other materials studied in the electrolytes PBS and SBF. Electron microscopy images revealed the presence of pitting on the surface of the CoCrMo sample and the presence of cavities in the Ti6Al4V alloy.